Exploring visual literacy skills and dispositions through a museum-sponsored online professional development for K-12 teachers. Issue 1 (2nd January 2021) - Schoonover, Nina R.
Abstract: This qualitative case study explored the experiences of two teachers participating in a visual literacy online professional development course sponsored by a state-funded art museum. As the world becomes more visual, there is a continued need for teachers to develop the skills needed to foster visual literacy in their students; therefore, the goal of this work was to amplify the experiences of these veteran teachers throughout the course, as well as in their classrooms, to reflect their growth throughout the program. Drawing primarily on Tishman's 'slow looking' and Perkins' (1994 ) concept of the 'intelligent eye' and the 'dispositions' for viewing art, the study was framed around the following research questions: 1) What are the experiences of teachers participating in an online visual literacy course? and 2) What dispositions do teachers take on when fostering visual literacy in their classrooms? The findings from this study highlight some of the difficulties the teachers faced, particularly in navigating an online terrain, but also some levels of discomfort with the visual literacy material. However, they also reveal how the two teachers found new ways to 'attend' to art, as well as new classroom skills and techniques they each brought back into their classrooms.